2011
DOI: 10.1007/s13197-011-0289-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of post-harvest calcium chloride dip treatment and gamma irradiation on storage quality and shelf-life extension of Red delicious apple

Abstract: Freshly harvested Red delicious apples were dipped in calcium chloride solution of varying concentrations (0.5-2.0% w/v) for 1 h prior to irradiation at dose level of 0.4 kGy. Fruits after radiation treatment were stored at 2 ± 1°C, RH 90% and evaluated at intervals of 30 days for various quality parameters. Results revealed significant (p ≤ 0.05) retention in firmness, juice yield and ascorbic acid content in samples treated with combination of calcium chloride at 2.0% w/v and gamma irradiation (0.4 kGy) duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
37
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 34 publications
4
37
0
1
Order By: Relevance
“…When these parts are weakened, there is an uncontrollable loss of water, which contributes to fruit decay [30]. Positive correlation among the application of Ca fertilizers and fruit storage ability has been conformed in results of many scientific studies [31][32][33]. Table 3 data also show that in the present study there was no statistical difference in TSS and acidity of apple fruits between examined variants.…”
Section: Methodssupporting
confidence: 83%
“…When these parts are weakened, there is an uncontrollable loss of water, which contributes to fruit decay [30]. Positive correlation among the application of Ca fertilizers and fruit storage ability has been conformed in results of many scientific studies [31][32][33]. Table 3 data also show that in the present study there was no statistical difference in TSS and acidity of apple fruits between examined variants.…”
Section: Methodssupporting
confidence: 83%
“…Ascorbic acid content decreased gradually during the storage of papaya slices, showing greater retention in fruit treated with HT‐Ca + Chit, followed by HT‐Ca, Chit, and Control. Consistent with these results, Djioua and others () found that the application of hydrothermal treatment on fresh‐cut mango decreased the content of vitamin C. Hussain and others () reported that increasing the calcium chloride concentration in apple maintained the content of ascorbic acid; they explained that the beneficial effect of calcium in preventing the loss of ascorbic acid during storage was due to the regulation of the oxidative process in the cytosol.…”
Section: Resultsmentioning
confidence: 58%
“…Preliminary test for hydrothermal treatment were conducted using conditions reported previously: calcium chloride concentration (0.5%, 1%, 2%, and 3%), temperature (49 °C, 55 °C, and 65 °C), and time (3 and 25 min; Eryani‐Raqeeb and others ; Leyva‐López and others ; Hussain and others ; Chávez‐Sánchez and others ). The selected conditions were 1% CaCl 2 , 49 °C, and 25 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Calcium ions make cell walls less accessible to enzymes that cause softening or to cell wall degrading enzymes produced by fungal pathogens. 13,14 Previously, we found that preharvest samples sprayed with 10 mM CaCl 2 increased the broccoli microgreen biomass by more than 50% and extended the shelf life significantly. 15 However, the effect of calcium treatment on the inner chemical profile changes, especially GL contents, has never been studied.…”
Section: ■ Introductionmentioning
confidence: 96%